FAO's Role in Achieving Food Security in Lower middle-income Arab countries - زيود , لين (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Research objective to highlight FAO's role In ensuring the eradication of hunger and the improvement of agriculture and agricultural development, with a view to improving the standard of living for all and the enjoyment of health, which is the second sustainable development goal, this organization has set its strategic objective for the period 2016/2030 in improving food security indicators and eliminating undernutrition and malnutrition in developing countries, as well as lighting up the extent to which middle-income Arab States have achieved the bottom line (nine States) for their food security, and their overreach of indicators of under nutrition and malnutrition. The researcher measured FAO's role in the programmers, plans and strategies developed to ensure that the Arab States in question ensured their food security and went beyond the problem of under nutrition and malnutrition of their citizens. The researcher relied on the globally adopted measure of food insecurity to measure food security availability indicators, and indicators to overcome the problem of under nutrition. The researcher followed the analytical descriptive approach, based on the organization's published data and reports, and reached the following findings: The Food and Agriculture Organization of the United Nations (FAO) has played the role required to ensure food security in the Arab States under consideration. It has prepared appropriate programmers and plans and has even developed long-term strategies. Food security is not available in middle-income Arab countries from the lower tranche. The sample countries in question have not exceeded the phenomenon of under nutrition and malnutrition, which has had a negative impact on the prevalence and prevalence of obesity among children under five years of age, as well as on the prevalence of anemia among women in the 15 to 49 age group.